Effect of temperature and leaf wetness on Phoma tarda and phoma leaf spot in coffee seedlings - Lorenzetti, Emi Rainildes; Pozza, Edson Ampélio; Souza, Paulo Estevão de; Santos, Leandro Alvarenga; Alves, Eduardo; Silva, André Costa; Maia, Fernanda Gonçalves Martins; Carvalho, Rejane Rodrigues da Costa (Coffee Science - ISSN 1984-3909, 2015)
Phoma leaf spot is a major disease of coffee plants in regions with specific conditions of temperature and humidity. Despite the importance of environmental variables for disease progression, so far they have been poorly understood. Thus, we assessed the effect of different temperatures (15, 20, 25 and 30 oC) on mycelial growth, production and germination of conidia of Phoma tarda; and the same effect of temperature (15, 20, 25 and 30 oC) and leaf wetness duration (6, 12, 24, 36 and 48 hours) on fungal infection and severity of disease over time in coffee plants. Disease assessment was integrated in the area using the disease progress curve (AUDPC) and the infection processes were observed by scanning electron microscopy (SEM). The optimal temperatures for fungus growth, conidial production and germination in vitro were 22.9, 29.8, and 25.1 °C, respectively. Temperatures ranging from 15-20 °C significantly increased germ tube length and provided favorable conditions for pathogen infection through observation of early events such as cuticle separation from leaf tissue. The same temperature range combined with increasing leaf wetness periods, reached the highest value of the AUDPC of phoma leaf spot. Thus, it was found that both temperature and leaf wetness duration in the variables assessed and the difference in relation to temperature for in vitro growth and sporulation for in vivo tests were important.